5(m+3)+2(m+8)=

Simple and best practice solution for 5(m+3)+2(m+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(m+3)+2(m+8)= equation:


Simplifying
5(m + 3) + 2(m + 8) = 0

Reorder the terms:
5(3 + m) + 2(m + 8) = 0
(3 * 5 + m * 5) + 2(m + 8) = 0
(15 + 5m) + 2(m + 8) = 0

Reorder the terms:
15 + 5m + 2(8 + m) = 0
15 + 5m + (8 * 2 + m * 2) = 0
15 + 5m + (16 + 2m) = 0

Reorder the terms:
15 + 16 + 5m + 2m = 0

Combine like terms: 15 + 16 = 31
31 + 5m + 2m = 0

Combine like terms: 5m + 2m = 7m
31 + 7m = 0

Solving
31 + 7m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-31' to each side of the equation.
31 + -31 + 7m = 0 + -31

Combine like terms: 31 + -31 = 0
0 + 7m = 0 + -31
7m = 0 + -31

Combine like terms: 0 + -31 = -31
7m = -31

Divide each side by '7'.
m = -4.428571429

Simplifying
m = -4.428571429

See similar equations:

| -5s=5-10s | | -3c+10c+2+-5= | | 0=x*2.5 | | 4x^2-14+2=0 | | 40+55h=190 | | 2k^4+12k^2+9=0 | | 0.3+y=2 | | 4x^2+44x-122=0 | | 6j+6=9j | | -5a+28a= | | 0=x/2.5 | | 9p-13p+12p+19q= | | 2(4.5+m)+3=4(m-3)+5.5 | | 2(4.5+m)+3=4(m-3)5.5 | | 2x+-1-6=10+-10x+6 | | 12d+5e-7d= | | 1=4.5-2p+2.333333p | | 5k(k-2)-8k=-34 | | 1+x-6x=11 | | 5x=2x+42 | | 4p+8p-p= | | -7y=9-10y | | -5t-4=2t+14 | | 5x+1y=112 | | 1.25x=15.25 | | 6w+12=48 | | (5x-2)(3x+4)=(3x-5)(5x+1)+15 | | 4x+152=6x+166 | | 4k^2+3k-7=0 | | 9p+5q-2p= | | X-3+8=20 | | 3p+9=6p |

Equations solver categories